Pengaruh Operating Capacity, Sales Growth, dan Arus Kas Operasi Terhadap Financial Distress : The Effect of Operating Capacity, Sales Growth, and Operational Cash Flow On Financial Distress - Miswaty; Novitasari, Dila (School of Business, Bogor Agricultural University (SB-IPB), 2023)
This study aims to examine the effect of Operating Capacity, Sales Growth, and Operating Cash Flow on Financial Distress in Service Companies in the Infrastructure, Utilities, and Transportation sectors listed on IDX period 2018-2020. The technique used in this study is purposive sampling which produced 40 samples companies in a period of 3 years. The analytical method used is multiple linier regression. The result of this study indicate that Operating Capacity and Operating Cash Flow affect Financial Distress, Sales Growth has no effect in Financial Distress. Implications for manager can realize facing financial distress like operating capacity, sales growth and operating cash flow and focus to maintain operating cash flow generating enough to drive the operating capacity needs of the business. There is also a clear implication for managers of firms as paying most of one attention to one aspect of financial performance appears to increase financial distress like operating capacity, sales growth and operating cash flows and managing operating cash flow according to the company’s capabilities. Investors and creditors also need to consider fundamental aspects such as the company’s financial ratios providing a better understanding of the performance of the the firmas operating capacity, sales growth, and operating cash flows to prediction of financial distress. Keywords: financial distress, operating capacity, cash flow, sales growth, IDX